src/HOL/Semiring_Normalization.thy
author haftmann
Fri, 07 May 2010 15:05:52 +0200
changeset 36751 7f1da69cacb3
parent 36720 src/HOL/Groebner_Basis.thy@41da7025e59c
child 36753 5cf4e9128f22
permissions -rw-r--r--
split of semiring normalization from Groebner theory; moved field_comp_conv to Numeral_Simproces

(*  Title:      HOL/Semiring_Normalization.thy
    Author:     Amine Chaieb, TU Muenchen
*)

header {* Semiring normalization *}

theory Semiring_Normalization
imports Numeral_Simprocs Nat_Transfer
uses
  "Tools/Groebner_Basis/normalizer.ML"
begin

setup Normalizer.setup

locale normalizing_semiring =
  fixes add mul pwr r0 r1
  assumes add_a:"(add x (add y z) = add (add x y) z)"
    and add_c: "add x y = add y x" and add_0:"add r0 x = x"
    and mul_a:"mul x (mul y z) = mul (mul x y) z" and mul_c:"mul x y = mul y x"
    and mul_1:"mul r1 x = x" and  mul_0:"mul r0 x = r0"
    and mul_d:"mul x (add y z) = add (mul x y) (mul x z)"
    and pwr_0:"pwr x 0 = r1" and pwr_Suc:"pwr x (Suc n) = mul x (pwr x n)"
begin

lemma mul_pwr:"mul (pwr x p) (pwr x q) = pwr x (p + q)"
proof (induct p)
  case 0
  then show ?case by (auto simp add: pwr_0 mul_1)
next
  case Suc
  from this [symmetric] show ?case
    by (auto simp add: pwr_Suc mul_1 mul_a)
qed

lemma pwr_mul: "pwr (mul x y) q = mul (pwr x q) (pwr y q)"
proof (induct q arbitrary: x y, auto simp add:pwr_0 pwr_Suc mul_1)
  fix q x y
  assume "\<And>x y. pwr (mul x y) q = mul (pwr x q) (pwr y q)"
  have "mul (mul x y) (mul (pwr x q) (pwr y q)) = mul x (mul y (mul (pwr x q) (pwr y q)))"
    by (simp add: mul_a)
  also have "\<dots> = (mul (mul y (mul (pwr y q) (pwr x q))) x)" by (simp add: mul_c)
  also have "\<dots> = (mul (mul y (pwr y q)) (mul (pwr x q) x))" by (simp add: mul_a)
  finally show "mul (mul x y) (mul (pwr x q) (pwr y q)) =
    mul (mul x (pwr x q)) (mul y (pwr y q))" by (simp add: mul_c)
qed

lemma pwr_pwr: "pwr (pwr x p) q = pwr x (p * q)"
proof (induct p arbitrary: q)
  case 0
  show ?case using pwr_Suc mul_1 pwr_0 by (induct q) auto
next
  case Suc
  thus ?case by (auto simp add: mul_pwr [symmetric] pwr_mul pwr_Suc)
qed

lemma semiring_ops:
  shows "TERM (add x y)" and "TERM (mul x y)" and "TERM (pwr x n)"
    and "TERM r0" and "TERM r1" .

lemma semiring_rules:
  "add (mul a m) (mul b m) = mul (add a b) m"
  "add (mul a m) m = mul (add a r1) m"
  "add m (mul a m) = mul (add a r1) m"
  "add m m = mul (add r1 r1) m"
  "add r0 a = a"
  "add a r0 = a"
  "mul a b = mul b a"
  "mul (add a b) c = add (mul a c) (mul b c)"
  "mul r0 a = r0"
  "mul a r0 = r0"
  "mul r1 a = a"
  "mul a r1 = a"
  "mul (mul lx ly) (mul rx ry) = mul (mul lx rx) (mul ly ry)"
  "mul (mul lx ly) (mul rx ry) = mul lx (mul ly (mul rx ry))"
  "mul (mul lx ly) (mul rx ry) = mul rx (mul (mul lx ly) ry)"
  "mul (mul lx ly) rx = mul (mul lx rx) ly"
  "mul (mul lx ly) rx = mul lx (mul ly rx)"
  "mul lx (mul rx ry) = mul (mul lx rx) ry"
  "mul lx (mul rx ry) = mul rx (mul lx ry)"
  "add (add a b) (add c d) = add (add a c) (add b d)"
  "add (add a b) c = add a (add b c)"
  "add a (add c d) = add c (add a d)"
  "add (add a b) c = add (add a c) b"
  "add a c = add c a"
  "add a (add c d) = add (add a c) d"
  "mul (pwr x p) (pwr x q) = pwr x (p + q)"
  "mul x (pwr x q) = pwr x (Suc q)"
  "mul (pwr x q) x = pwr x (Suc q)"
  "mul x x = pwr x 2"
  "pwr (mul x y) q = mul (pwr x q) (pwr y q)"
  "pwr (pwr x p) q = pwr x (p * q)"
  "pwr x 0 = r1"
  "pwr x 1 = x"
  "mul x (add y z) = add (mul x y) (mul x z)"
  "pwr x (Suc q) = mul x (pwr x q)"
  "pwr x (2*n) = mul (pwr x n) (pwr x n)"
  "pwr x (Suc (2*n)) = mul x (mul (pwr x n) (pwr x n))"
proof -
  show "add (mul a m) (mul b m) = mul (add a b) m" using mul_d mul_c by simp
next show"add (mul a m) m = mul (add a r1) m" using mul_d mul_c mul_1 by simp
next show "add m (mul a m) = mul (add a r1) m" using mul_c mul_d mul_1 add_c by simp
next show "add m m = mul (add r1 r1) m" using mul_c mul_d mul_1 by simp
next show "add r0 a = a" using add_0 by simp
next show "add a r0 = a" using add_0 add_c by simp
next show "mul a b = mul b a" using mul_c by simp
next show "mul (add a b) c = add (mul a c) (mul b c)" using mul_c mul_d by simp
next show "mul r0 a = r0" using mul_0 by simp
next show "mul a r0 = r0" using mul_0 mul_c by simp
next show "mul r1 a = a" using mul_1 by simp
next show "mul a r1 = a" using mul_1 mul_c by simp
next show "mul (mul lx ly) (mul rx ry) = mul (mul lx rx) (mul ly ry)"
    using mul_c mul_a by simp
next show "mul (mul lx ly) (mul rx ry) = mul lx (mul ly (mul rx ry))"
    using mul_a by simp
next
  have "mul (mul lx ly) (mul rx ry) = mul (mul rx ry) (mul lx ly)" by (rule mul_c)
  also have "\<dots> = mul rx (mul ry (mul lx ly))" using mul_a by simp
  finally
  show "mul (mul lx ly) (mul rx ry) = mul rx (mul (mul lx ly) ry)"
    using mul_c by simp
next show "mul (mul lx ly) rx = mul (mul lx rx) ly" using mul_c mul_a by simp
next
  show "mul (mul lx ly) rx = mul lx (mul ly rx)" by (simp add: mul_a)
next show "mul lx (mul rx ry) = mul (mul lx rx) ry" by (simp add: mul_a )
next show "mul lx (mul rx ry) = mul rx (mul lx ry)" by (simp add: mul_a,simp add: mul_c)
next show "add (add a b) (add c d) = add (add a c) (add b d)"
    using add_c add_a by simp
next show "add (add a b) c = add a (add b c)" using add_a by simp
next show "add a (add c d) = add c (add a d)"
    apply (simp add: add_a) by (simp only: add_c)
next show "add (add a b) c = add (add a c) b" using add_a add_c by simp
next show "add a c = add c a" by (rule add_c)
next show "add a (add c d) = add (add a c) d" using add_a by simp
next show "mul (pwr x p) (pwr x q) = pwr x (p + q)" by (rule mul_pwr)
next show "mul x (pwr x q) = pwr x (Suc q)" using pwr_Suc by simp
next show "mul (pwr x q) x = pwr x (Suc q)" using pwr_Suc mul_c by simp
next show "mul x x = pwr x 2" by (simp add: nat_number' pwr_Suc pwr_0 mul_1 mul_c)
next show "pwr (mul x y) q = mul (pwr x q) (pwr y q)" by (rule pwr_mul)
next show "pwr (pwr x p) q = pwr x (p * q)" by (rule pwr_pwr)
next show "pwr x 0 = r1" using pwr_0 .
next show "pwr x 1 = x" unfolding One_nat_def by (simp add: nat_number' pwr_Suc pwr_0 mul_1 mul_c)
next show "mul x (add y z) = add (mul x y) (mul x z)" using mul_d by simp
next show "pwr x (Suc q) = mul x (pwr x q)" using pwr_Suc by simp
next show "pwr x (2 * n) = mul (pwr x n) (pwr x n)" by (simp add: nat_number' mul_pwr)
next show "pwr x (Suc (2 * n)) = mul x (mul (pwr x n) (pwr x n))"
    by (simp add: nat_number' pwr_Suc mul_pwr)
qed


lemmas normalizing_semiring_axioms' =
  normalizing_semiring_axioms [normalizer
    semiring ops: semiring_ops
    semiring rules: semiring_rules]

end

sublocale comm_semiring_1
  < normalizing!: normalizing_semiring plus times power zero one
proof
qed (simp_all add: algebra_simps)

declaration {* Normalizer.semiring_funs @{thm normalizing.normalizing_semiring_axioms'} *}

locale normalizing_ring = normalizing_semiring +
  fixes sub :: "'a \<Rightarrow> 'a \<Rightarrow> 'a"
    and neg :: "'a \<Rightarrow> 'a"
  assumes neg_mul: "neg x = mul (neg r1) x"
    and sub_add: "sub x y = add x (neg y)"
begin

lemma ring_ops: shows "TERM (sub x y)" and "TERM (neg x)" .

lemmas ring_rules = neg_mul sub_add

lemmas normalizing_ring_axioms' =
  normalizing_ring_axioms [normalizer
    semiring ops: semiring_ops
    semiring rules: semiring_rules
    ring ops: ring_ops
    ring rules: ring_rules]

end

sublocale comm_ring_1
  < normalizing!: normalizing_ring plus times power zero one minus uminus
proof
qed (simp_all add: diff_minus)

declaration {* Normalizer.semiring_funs @{thm normalizing.normalizing_ring_axioms'} *}

locale normalizing_field = normalizing_ring +
  fixes divide :: "'a \<Rightarrow> 'a \<Rightarrow> 'a"
    and inverse:: "'a \<Rightarrow> 'a"
  assumes divide_inverse: "divide x y = mul x (inverse y)"
     and inverse_divide: "inverse x = divide r1 x"
begin

lemma field_ops: shows "TERM (divide x y)" and "TERM (inverse x)" .

lemmas field_rules = divide_inverse inverse_divide

lemmas normalizing_field_axioms' =
  normalizing_field_axioms [normalizer
    semiring ops: semiring_ops
    semiring rules: semiring_rules
    ring ops: ring_ops
    ring rules: ring_rules
    field ops: field_ops
    field rules: field_rules]

end

locale normalizing_semiring_cancel = normalizing_semiring +
  assumes add_cancel: "add (x::'a) y = add x z \<longleftrightarrow> y = z"
  and add_mul_solve: "add (mul w y) (mul x z) =
    add (mul w z) (mul x y) \<longleftrightarrow> w = x \<or> y = z"
begin

lemma noteq_reduce: "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> add (mul a c) (mul b d) \<noteq> add (mul a d) (mul b c)"
proof-
  have "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> \<not> (a = b \<or> c = d)" by simp
  also have "\<dots> \<longleftrightarrow> add (mul a c) (mul b d) \<noteq> add (mul a d) (mul b c)"
    using add_mul_solve by blast
  finally show "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> add (mul a c) (mul b d) \<noteq> add (mul a d) (mul b c)"
    by simp
qed

lemma add_scale_eq_noteq: "\<lbrakk>r \<noteq> r0 ; (a = b) \<and> ~(c = d)\<rbrakk>
  \<Longrightarrow> add a (mul r c) \<noteq> add b (mul r d)"
proof(clarify)
  assume nz: "r\<noteq> r0" and cnd: "c\<noteq>d"
    and eq: "add b (mul r c) = add b (mul r d)"
  hence "mul r c = mul r d" using cnd add_cancel by simp
  hence "add (mul r0 d) (mul r c) = add (mul r0 c) (mul r d)"
    using mul_0 add_cancel by simp
  thus "False" using add_mul_solve nz cnd by simp
qed

lemma add_r0_iff: " x = add x a \<longleftrightarrow> a = r0"
proof-
  have "a = r0 \<longleftrightarrow> add x a = add x r0" by (simp add: add_cancel)
  thus "x = add x a \<longleftrightarrow> a = r0" by (auto simp add: add_c add_0)
qed

declare normalizing_semiring_axioms' [normalizer del]

lemmas normalizing_semiring_cancel_axioms' =
  normalizing_semiring_cancel_axioms [normalizer
    semiring ops: semiring_ops
    semiring rules: semiring_rules
    idom rules: noteq_reduce add_scale_eq_noteq]

end

locale normalizing_ring_cancel = normalizing_semiring_cancel + normalizing_ring + 
  assumes subr0_iff: "sub x y = r0 \<longleftrightarrow> x = y"
begin

declare normalizing_ring_axioms' [normalizer del]

lemmas normalizing_ring_cancel_axioms' = normalizing_ring_cancel_axioms [normalizer
  semiring ops: semiring_ops
  semiring rules: semiring_rules
  ring ops: ring_ops
  ring rules: ring_rules
  idom rules: noteq_reduce add_scale_eq_noteq
  ideal rules: subr0_iff add_r0_iff]

end

sublocale idom
  < normalizing!: normalizing_ring_cancel plus times power zero one minus uminus
proof
  fix w x y z
  show "w * y + x * z = w * z + x * y \<longleftrightarrow> w = x \<or> y = z"
  proof
    assume "w * y + x * z = w * z + x * y"
    then have "w * y + x * z - w * z - x * y = 0" by (simp add: algebra_simps)
    then have "w * (y - z) - x * (y - z) = 0" by (simp add: algebra_simps)
    then have "(y - z) * (w - x) = 0" by (simp add: algebra_simps)
    then have "y - z = 0 \<or> w - x = 0" by (rule divisors_zero)
    then show "w = x \<or> y = z" by auto
  qed (auto simp add: add_ac)
qed (simp_all add: algebra_simps)

declaration {* Normalizer.semiring_funs @{thm normalizing.normalizing_ring_cancel_axioms'} *}

interpretation normalizing_nat!: normalizing_semiring_cancel
  "op +" "op *" "op ^" "0::nat" "1"
proof (unfold_locales, simp add: algebra_simps)
  fix w x y z ::"nat"
  { assume p: "w * y + x * z = w * z + x * y" and ynz: "y \<noteq> z"
    hence "y < z \<or> y > z" by arith
    moreover {
      assume lt:"y <z" hence "\<exists>k. z = y + k \<and> k > 0" by (rule_tac x="z - y" in exI, auto)
      then obtain k where kp: "k>0" and yz:"z = y + k" by blast
      from p have "(w * y + x *y) + x*k = (w * y + x*y) + w*k" by (simp add: yz algebra_simps)
      hence "x*k = w*k" by simp
      hence "w = x" using kp by simp }
    moreover {
      assume lt: "y >z" hence "\<exists>k. y = z + k \<and> k>0" by (rule_tac x="y - z" in exI, auto)
      then obtain k where kp: "k>0" and yz:"y = z + k" by blast
      from p have "(w * z + x *z) + w*k = (w * z + x*z) + x*k" by (simp add: yz algebra_simps)
      hence "w*k = x*k" by simp
      hence "w = x" using kp by simp }
    ultimately have "w=x" by blast }
  thus "(w * y + x * z = w * z + x * y) = (w = x \<or> y = z)" by auto
qed

declaration {* Normalizer.semiring_funs @{thm normalizing_nat.normalizing_semiring_cancel_axioms'} *}

locale normalizing_field_cancel = normalizing_ring_cancel + normalizing_field
begin

declare normalizing_field_axioms' [normalizer del]

lemmas normalizing_field_cancel_axioms' = normalizing_field_cancel_axioms [normalizer
  semiring ops: semiring_ops
  semiring rules: semiring_rules
  ring ops: ring_ops
  ring rules: ring_rules
  field ops: field_ops
  field rules: field_rules
  idom rules: noteq_reduce add_scale_eq_noteq
  ideal rules: subr0_iff add_r0_iff]

end

sublocale field 
  < normalizing!: normalizing_field_cancel plus times power zero one minus uminus divide inverse
proof
qed (simp_all add: divide_inverse)

declaration {* Normalizer.field_funs @{thm normalizing.normalizing_field_cancel_axioms'} *}

end